Analisis Laporan Keuangan Menggunakan Metode Horizontal, Vertikal, Ratio untuk Menilai Kinerja Keuangan pada PT. Tower Bersama Infrastructure Tbk - Yulianti, Putri; Fauziah Dasuki, Poppy; Dian Agustin, Rahma; Amelia, Riska; Kusuma Dewi Al-Ayyubi, Rizna; Novi Fadhila, Alfitri; Sulistiyo, Hari (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
This study aims to assess the financial performance of PT Tower Bersama Infrastructure Tbk (TBIG) from 2022 to 2023 using quantitative research methods through financial statement analysis. TBIG is one of the leading telecommunications infrastructure companies in Indonesia that has experienced significant business changes during that period. Based on financial statement data, although the company's revenue increased slightly in 2023, net profit actually decreased by around 20% compared to the previous year. This decrease was caused by an increase in the cost of revenue, high interest costs, and slowing growth in the telecommunications sector due to operator mergers. This research method utilizes secondary data obtained from the Indonesia Stock Exchange (IDX) in the form of TBIG's financial statements for the 2022 and 2023 periods. The analysis was conducted by comparing financial ratios covering liquidity, solvency, profitability, and operational efficiency using horizontal, vertical, and ratio approaches. The results show that the company's liquidity remains stable, but its solvency decreases due to an increase in short-term liabilities. Profitability also decreased, as evidenced by a decrease in net profit margin, gross profit margin, and net operating margin. Overall, TBIG's financial performance remains quite strong and maintains operational performance, but it faces challenges in managing its debt structure and maintaining long-term profitability. This research is expected to provide insight to management, investors, and other stakeholders in making strategic decisions related to the company's financial condition.